Qualitative Analysis of the Role of General Practitioners in the Health Care Referral System - Fadhilat Try Rejeki; Andi Muhammad Ali Haedar Azhar (Nusantara Sehat: Jurnal Kesehatan Indonesia, 2025)
ABSTRACT This study aims to explore the qualitative role of general practitioners (GPs) in the healthcare referral system, emphasizing their strategic function as coordinators and gatekeepers in ensuring accessible, efficient, and continuous healthcare services. The research employs a qualitative descriptive approach through a literature-based study, utilizing data from academic journals, books, and official reports published between 2015 and 2025. Data collection was conducted using systematic literature tracing and document analysis, while data analysis involved thematic identification, data reduction, categorization, and inductive interpretation. The findings reveal that GPs are central actors in coordinating patient care, determining referral appropriateness, and bridging communication between primary and secondary healthcare providers. The effectiveness of referral practices is influenced by factors such as communication quality, system infrastructure, professional competence, and policy support. Moreover, the implementation of e-referral systems and interprofessional collaboration has significantly enhanced the efficiency and transparency of referral processes. However, challenges such as administrative burden, uneven access to specialists, and limited training in complex case management persist. The study concludes that strengthening GP autonomy, improving digital integration, and reinforcing continuous professional development are essential strategies to optimize referral systems. These findings contribute to the theoretical development of primary healthcare and offer practical insights for improving policy and clinical coordination. Keywords: general practitioners, referral system, primary healthcare, qualitative research, coordination.